A Long Story Short: An Analysis of Instagram Stories during the 2020 Campaigns. Issue 3 (2nd October 2022) - Towner, Terri L.; Muñoz, Caroline Lego
ABSTRACT: Political campaigns are becoming immensely visual, with many platforms, such as YouTube, Instagram, and SnapChat, employed by candidates. We focus on the second most popular platform, Instagram, examining how the 2020 presidential candidates, Donald Trump and Joe Biden, utilize "Stories" in their digital campaigns. Instagram "Stories" allow users to capture and post related images and videos in a slideshow format that disappears after 24-hours. Yet, how did the candidates utilize the Instagram Story technology affordances, such as location tags, stickers, swipe up/websites, and hashtags? What political messages – attack, behind the scenes, or rally - did the candidates use both before and after Election Day? How do the candidates differ in the Story messages? Through the technology affordances lens, we conduct a quantitative content analysis of Instagram Stories posted by Trump and Biden one week before and after Election Day 2020. Our findings reveal how the possible actions or affordances linked to the "Story" feature allow candidates to communicate and engage with users. We conclude by offering a set of industry recommendations when using Instagram Stories in campaigns.